2020
DOI: 10.1111/add.15050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UK plain tobacco packaging and minimum pack size legislation on tobacco and nicotine product switching behaviour

Abstract: Background and aims The introduction of plain tobacco packaging and minimum pack size legislation in the United Kingdom between May 2016 and May 2017 was accompanied by substantial changes in tobacco product diversity and pricing. This study investigates the extent to which these changes were associated with consumer switching between tobacco product types and price segments, and from tobacco to non‐tobacco nicotine products. Design Longitudinal study (changing trends in product and price choices) and survey (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…However, other studies found relatively lower compliance in Indonesia (December 2017) ( 16 ). Furthermore, while countries like the United Kingdom and Sri Lanka have banned single cigarettes ( 21 , 22 ), other countries like Indonesia and India have not ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found relatively lower compliance in Indonesia (December 2017) ( 16 ). Furthermore, while countries like the United Kingdom and Sri Lanka have banned single cigarettes ( 21 , 22 ), other countries like Indonesia and India have not ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from a representative UK consumer panel conducted before the minimum pack size regulation took effect, around 68% of FM cigarette pack sizes purchased included between 11 and 19 sticks, and roughly 13% contained 10 sticks. 10 These data indicate that most people smoking FM cigarettes would have had to switch to larger pack sizes after the policy implementation. In contrast, the effect on RYO tobacco purchases was less pronounced.…”
Section: Original Researchmentioning
confidence: 99%
“…Prior to the regulation, around 60% of RYO purchases were already packs containing more than 30 g, and 12.5 g to 29 g and <12.5 g pack sizes were at only about 15% each. 10 It is important to investigate whether the introduction of minimum pack sizes has led to an increase in daily cigarette consumption among people smoking cigarettes given the direct and indirect health benefits of smoking reduction. In a metaanalysis, Chang et al 11 found that reducing cigarette consumption from heavy to moderate, or by at least 50%, significantly decreased lung cancer risk.…”
Section: Original Researchmentioning
confidence: 99%
“…Evidence from Australia, which in 2012 became the first country to introduce standardised packaging, suggests that implementation led to an increase in quitline calls [8] and increased the rate of decline in smoking prevalence [9]. Research on the introduction of standardised packaging in England has demonstrated that implementation has been associated with considerable increases in the price of tobacco products, switching to less expensive tobacco products and increased use of e-cigarettes among smokers [10][11][12][13]. However, the effect of standardised packaging on smoking prevalence in England has not yet been explored by researchers independent of the tobacco industry's funding.…”
Section: Introductionmentioning
confidence: 99%